2017
DOI: 10.1016/j.talanta.2016.08.079
|View full text |Cite
|
Sign up to set email alerts
|

Matrix isolation with an ion transfer device for interference-free simultaneous spectrophotometric determinations of hexavalent and trivalent chromium in a flow-based system

Abstract: Chromium speciation by spectrophotometric determination of hexavalent chromium (Cr(VI)) with diphenylcarbazide (DPC) has several problems. These include: (1) the inability to directly detect trivalent chromium (Cr(III)) with DPC, (2) positive interference in Cr(VI) determination by other metal cations and (3) negative interference by any reducing agent present in the sample. These are addressed with an ion transfer device (ITD) in a flow injection analysis system. We previously developed the ITD for electrodia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…34 The spectrophotometry using DPC as the chromogenic agent for Cr(VI) determination is approved as a standard analytical method in many countries, and it has been used for more than one century due to its high sensitivity and selectivity. 35,36 As shown in Fig. S2, (ESI †) the reaction mixture of DPC and Cr(VI) has a strong absorption peak at the wavelength of 540 nm.…”
Section: Analytical Performance Of the Absorbance Modementioning
confidence: 99%
See 1 more Smart Citation
“…34 The spectrophotometry using DPC as the chromogenic agent for Cr(VI) determination is approved as a standard analytical method in many countries, and it has been used for more than one century due to its high sensitivity and selectivity. 35,36 As shown in Fig. S2, (ESI †) the reaction mixture of DPC and Cr(VI) has a strong absorption peak at the wavelength of 540 nm.…”
Section: Analytical Performance Of the Absorbance Modementioning
confidence: 99%
“…Because the ratiometric brightness signal is insensitive to the variations in light source intensity and shooting parameters of the camera, the portable dual-mode device offers good baseline stability for absorbance and ratiometric fluorescence measurements. The availability of the ratiometric fluorescence and absorbance modes was tested by using rhodamine 6G (R6G) and 1,5-diphenylcarbazide (DPC)-Cr(VI) system 31,32 as the models, respectively. The application of the dual-mode portable device was demonstrated by the determination of hypochlorous acid by using a heptamethine cyanine-based fluorescent and colorimetric probe (Cy-ANP).…”
Section: Introductionmentioning
confidence: 99%
“…The electrodialytic ion transfer device (ITD) used in this study is as same as previously reported. 7,8 The ITD consists of five thin solution channels, which are separated by ion-permeable membranes (dialysis or ion exchange membranes). The sample solution was pumped through the center channel at 0.1 mL min -1 with a peristaltic pump (Minipuls 3, www.gilson.com).…”
Section: Ion Transfer Device Flow System and Detectormentioning
confidence: 99%
“…In addition, we found the combination of a flow injection and flow-batch system and SIA for Cr(VI). 133,134 Moreover, lab-in-syringe and SIA systems were proposed for speciation analysis 135 and lab-on-valve sequential injection ELISA for the determination of carbamazepine. 136 The microfluidic platform still becoming important for developing new methods for environmental applications.…”
Section: Application Of Flow-based System For Environmental Monitoringmentioning
confidence: 99%